Bidirectional decision analysis of online Ride-hailing enterprises based on fuzzy theory and cloud model - Mingliang Yu; Gengsheng Zhao; Zhanxin Ma; Dongping Pu (Scientific Reports)
Abstract At present, quantitative data is mainly used as the basis for service-oriented enterprise decision-making. However, a single dimension and type of analysis cannot accurately reflect the uncertainty of enterprise operations. To solve this problem, a hybrid decision method based on fuzzy analytic hierarchy process (F-AHP) and two-dimensional cloud model is constructed, aiming to help service-oriented enterprises represented by online ride-hailing (ORH) optimize their strategies to adapt to the changing market. Firstly, a multi-layer index system is constructed from the two key dimensions of enterprise management and user service, and F-AHP is introduced to calculate the weight of each index, which weakens the fuzziness of human subjective judgment based on comprehensive analysis from the inside out. Secondly, four ORH enterprises are taken as examples; survey data and standard score intervals are qualitatively expressed through the two-dimensional backward cloud generator. Finally, the two-dimensional forward cloud generator is used to quantitatively evaluate the comprehensive situation of each ORH enterprise. The proposed method realizes effective conversion between quantitative description and qualitative concepts, and its effectiveness is verified by comparing it with existing methods. The results show that gaps among ORH enterprises are mainly concentrated in management rather than in service. Market performance largely determines an enterprise’s basic operation scale, while user service quality determines its future development space.